Antibacterial mechanisms of bacteriocin BM1157 against Escherichia coli and Cronobacter sakazakii. (May 2021) - Luo, Lingli; Yi, Lanhua; Chen, Jiaxin; Liu, Bianfang; Lü, Xin
Abstract: E. coli and C. sakazakii are both opportunistic pathogenic bacteria that widely found in food. Emerging of antibiotic resistance makes the treatment of Gram-negative bacteria infection become ever more difficult. Therefore, it is urgent to find new antibacterial compounds against Gram-negative bacteria. Our previous study showed that bacteriocin BM1157 had broad antibacterial activity against both Gram-positive and Gram-negative bacteria. However, its antimicrobial mechanism against Gram-negative bacteria is still unknown. In this study, propidium iodide uptake and lactate dehydrogenase release experiments showed that the membrane integrity and permeability of the two indicator strains were not affected by BM1157 treatment. Observation of the ultrastructure of both bacteria by SEM and TEM also indicated that BM1157 did not damage the cell membrane. However, it significantly inhibited the biofilm formation of both bacteria. Furthermore, the lable-free proteome showed that BM1157 disturbed the carbohydrate metabolism, amino acid metabolism, lipid metabolism and nucleic acid metabolism, and then bioactive molecule synthesis and intracellular metabolism were blocked, resulting in cell death. Down-regulation of gene expression was further confirmed by real-time quantitative PCR. This study indicates that bacteriocin BM1157 inhibited Gram-negative bacteria by non-pore mechanisms. Highlights: BM1157 kill Escherichia coli and Cronobacter sakazakii. The cell membrane cannot be damaged after BM1157-treatment. BM1157 causes the cell metabolism of E. coli to be blocked.